Advanced issues in the economics of emerging markets - Barnett, William A.; Sergi, Bruno S. (Emerald Publishing Limited, 2020)
Volume 27 of the International Symposia in Economic Theory and Econometrics series collects a range of unique and diverse chapters, each investigating different spheres of development in emerging markets with a specific focus on significant engines of growth and advancement in the Asia-Pacific economies. Looking at the most sensitive issues behind economic growth in emerging markets, and particularly their long-term prospects, the chapters included in this volume explore the newest fields of research to understand the potential of these markets better. Including chapters from leading scholars worldwide, the volume provides comprehensive coverage of the key topics in fields spanning SMEs, terrorism, manufacturing waste reduction, financial literacy, female empowerment, leadership and corporate management, and the relationship between environmental, social, governance, and firm value. For students, researchers and practitioners, this volume offers a dynamic reference resource on emerging markets across a diverse range of topics.
Includes index.
Keywords: Economic development -- Pacific Area.; Marketing -- Pacific Area.; Business & Economics -- Development -- Economic Development.; Economic growth.; elektronické knihy; electronic books